Development of a three-load component instrumented stem for road cycling - Drouet, J. -M.; Champoux, Y. (Procedia Engineering, 2012)
The aim of this research was to develop an instrumented road bike stem to enable in situ measurements of static and dynamic loads transmitted through the stem-handlebar connection. Our stem is instrumented with twelve strain gauges and enables measurement of the vertical force and two moment components. Calibration and in situ measurements demonstrated that the instrumented stem provides accurate measurements for small and large loads. This paper presents the results for stem loads when climbing a hill out of the saddle and during road impact.